Peran RRI Boven Digoel Dalam Penyebaran Informasi Di Wilayah Perbatasan Indonesia Papua Nugini’ - Zalfah Alin Syarif (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
Radio Republik Indonesia is a national media with a role to disseminate information to the public, of course the role of radio in border areas is the responsibility of the government not only to disseminate information but also to maintain the state's security belt. Indonesia is currently still in the category of a developing country which results in Indonesia still experiencing many blank spots of information services so that information or broadcasts that connect the government and the community are not well received. This makes researchers conduct research on how the role of RRI Boven Digoel media in the dissemination of information in border areas, this is one of the functions of media services to the community. This study uses the Theory of Management Functions According to G.R Terry. By using qualitative descriptive research. The results of this study are as follows, Planning for the broadcast program of RRI Boven Digoel in the Indonesia-Papua New Guinea border area before making a new program for RRI always involves various elements of the surrounding community. This is so that there will be no social inequality or envy among the various tribes in the Boven Digoel area. In organizing RRI Boven Digoel, managing information in border areas according to researchers is still lacking, because it can be seen from the history of the leadership of LPP RRI which often changes leaders. RRI's role in positioning itself as a medium in building a sense of nationalism in border areas has been maximized because almost all of RRI's broadcast contents promote a sense of nationalism in border communities.